Campo e identidade: as regras do jogo publicitário - Lopes, Felipe Tavares Paes (2007)
In this dissertation, we discussed the pertinence of French sociologist Pierre Bourdieu s concept of social field as a theoretical tool for the scientific analysis of the advertising practice in Brazil nowadays. In other words, we analyzed if the production universe of this practice is characteristic of a hierarchical social environment organized according to specific interest logic and presenting tangential points with other social universes. We investigated if it is a relatively autonomous space, a kind of microcosm which operates like a force field, in which there are fights for its transformation or conservation. A kind of society with its own bonds, rules and consecration institutions within our society. To achieve this purpose, we analyzed the identitarian speeches of its agents - the meanings that advertising students and professionals share about this practice considering their positions in the social structure. This analysis allowed us to investigate if this correlation indicates the existence of an advertising field